Analyses of the three 1-Cys Peroxiredoxins from Aspergillus fumigatus reveal that cytosolic Prx1 is central to H2O2 metabolism and virulence - Marina Campos Rocha (Nature Portfolio, 2018)
Abstract Standing among the front defense strategies against pathogens, host phagocytic cells release various oxidants. Therefore, pathogens have to cope with stressful conditions at the site of infection. Peroxiredoxins (Prx) are highly reactive and abundant peroxidases that can support virulence and persistence of pathogens in distinct hosts. Here, we revealed that the opportunistic human pathogen A. fumigatus presents three 1-Cys Prx (Prx6 subfamily), which is unprecedented. We showed that PrxB and PrxC were in mitochondria, while Prx1 was in cytosol. As observed for other Prxs, recombinant Prx1 and PrxC decomposed H2O2 at elevated velocities (rate constants in the 107 M−1s−1 range). Deletion mutants for each Prx displayed higher sensitivity to oxidative challenge in comparison with the wild-type strain. Additionally, cytosolic Prx1 was important for A. fumigatus survival upon electron transport dysfunction. Expression of Prxs was dependent on the SakAHOG1 MAP kinase and the Yap1YAP1 transcription factor, a global regulator of the oxidative stress response in fungi. Finally, cytosolic Prx1 played a major role in pathogenicity, since it is required for full virulence, using a neutropenic mouse infection model. Our data indicate that the three 1-Cys Prxs act together to maintain the redox balance of A. fumigatus.